Pergeseran Bentuk Layanan Perpustakaan dan Peran Pustakawan Dalam Konsep Libraries Without Walls - Luthfi Nur Hakim; Angga Hadiapurwa (IAIN Ponorogo, 2022)
This research’s objective is to explains what impact libraries without walls have in library service and role of librarian. The research is qualitative research with literature study as the method. The results of the study revealed that several distance services emerged such as digital collection services, online collection searches, online webinars, dissemination of information and library news through social media and special services owned by certain libraries such as independent uploading for scientific works by users services and online plagiarism check services as well as the role of librarians in the concept of libraries without walls such as conventional roles, educators and influencers to increase literacy, technical librarians, and embedded librarians.